Virtual harm reduction efforts for Internet gambling: effects of deposit limits on actual Internet sports gambling behavior - Nelson Sarah E; LaPlante Debi A; Broda Anja; LaBrie Richard A; Bosworth Leslie B; Shaffer Howard J (BMC, 2008)
Abstract Background In an attempt to reduce harm related to gambling problems, an Internet sports betting service provider, bwin Interactive Entertainment, AG (bwin), imposes limits on the amount of money that users can deposit into their online gambling accounts. We examined the effects of these limits on gambling behavior. Methods We compared (1) gambling behavior of those who exceeded deposit limits with those who did not, and (2) gambling behavior before and after exceeding deposit limits. We analyzed 2 years of the actual sports gambling behavior records of 47000 subscribers to bwin. Results Only 160 (0.3%) exceeded deposit limits at least once. Gamblers who exceeded deposit limits evidenced higher average number of bets per active betting day and higher average size of bets than gamblers who did not exceed deposit limits. Comparing the gambling behavior before and after exceeding deposit limits revealed slightly more unfavorable gambling behavior after exceeding deposit limits. Conclusion Our findings indicate that Internet gamblers who exceed deposit limits constitute a group of bettors willing to take high risks; yet, surprisingly, they appear to do this rather successfully because their percentage of losses is lower than others in the sample. However, some of these gamblers exhibit some poor outcomes. Deposit limits might be necessary harm reduction measures to prevent the loss of extremely large amounts of money and cases of bankruptcy. We discuss how these limits might be modified based on our findings.